Clinical practice guidelines for the diagnosis and management of Duchenne muscular dystrophy: a scoping review - Malaga, Marco; Rodriguez-Calienes, Aaron; Chavez-Ecos, Fabian A.; Huerta-Rosario, Andrely; Alvarado-Gamarra, Giancarlo; Cabanillas-Lazo, Miguel; Moran-Ballon, Paula; Velásquez-Rimachi, Victor; Martinez-Esteban, Peggy; Alva-Diaz, Carlos (Frontiers in Neurology, 2024)
Introduction Our objective was to identify recent CPGs for the diagnosis and management of DMD and summarize their characteristics and reliability. Methods We conducted a scoping review of CPGs using MEDLINE, the Turning Research Into Practice (TRIP) database, Google Scholar, guidelines created by organizations, and other repositories to identify CPGs published in the last 5 years. Our protocol was drafted using the Preferred Reporting Items for Systematic Reviews and Meta-analyses for scoping reviews. To assess the reliability of the CPGs, we used all the domains included in the Appraisal of Guidelines Research and Evaluation II. Results We selected three CPGs published or updated between 2015 and 2020. All the guidelines showed good or adequate methodological rigor but presented pitfalls in stakeholder involvement and applicability domains. Recommendations were coherent across CPGs on steroid treatment, except for minor differences in dosing regimens. However, the recommendations were different for new drugs. Discussion There is a need for current and reliable CPGs that develop broad topics on the management of DMD and consider the challenges of developing recommendations for RDs.